132 Improved survival and outcome of HLA-mismatched donor hematopoietic stem cell transplantation in children with primary immunodeficiencies using new graft manipulation strategies in the UK. (December 2018) - Elfeky, R; Shah, RM; Unni, MNM; Rao, K; Chiesa, R; Amrolia, P; Worth, A; Flood, T; Abinun, M; Nademi, Z; Hambleton, S; Cant, AJ; et al.
Abstract : Background: Mismatched related and unrelated donor stem cell transplantation is considered a high risk transplant associated with high risk of graft loss, graft versus host disease (GvHD) and transplant related mortality (TRM). Alternative graft manipulation strategies have been employed over the last 10 years to reduce these risks, and here we present an analysis of these strategies in primary immunodeficiency (PID). Methods: Between 2006–2017, 147 PID patients received 155 mismatched grafts; 30 TCRαβ/CD19 depleted, 43 Cord (72% with no serotherapy), 17 CD34 +selection with T cell add-back and 65 unmanipulated bone marrow or peripheral blood stem cell grafts. Results: The estimated 8 year survival of the entire cohort was 79%, TRM was 21.7% and graft failure rate was 6%. Comparable rates of survival were recorded among different graft manipulation strategies. Post-transplant viral reactivation, aGvHD grades II-IV and chronic GvHD complicated 49.6%, 35% and 15% of the transplants, respectively. The use of TCR αβ/CD19 depletion in this study has reduced the occurrence of grade II-IV aGvHD among mismatched transplants: 40% among CD34+/T cell add-back to 11.5% with TCR αβ/CD19 depleted grafts. The same pattern was seen in terms of cGvHD where none of the recipients of TCR αβ/CD19 depleted grafts had cGvHD compared to 38.4% amongst CD34+/T cell add-back. However, one drawback of TCR αβ/CD19 depleted HSCT was the increased incidence of post-transplant viraemia reaching 70% versus 37%–49% among other graft manipulations. T cell immune reconstitution was robust among cord transplants however with a high incidence of aGvHD grade II-IV 56.7%. Stable full donor engraftment was significantly higher at 80% among TCRαβ+/CD19 +depleted and cord transplants versus 40%–60% among the other groups. Conclusions: Rapidly accessible cord and haploidentical grafts are suitable alternatives for patients with no HLA matched donor. Cord transplantation without serotherapy and TCRαβ+/CD19 +depleted grafts produced comparable survival rates of around 80% and exhibited higher donor chimerism compared to other strategies of graft manipulation.